Substrate Integrated Waveguide-Fed Tapered Slot Antenna With Smooth Performance Characteristics Over an Ultra-Wide Bandwidth - Locke, Lisa S.; Bornemann, Jens; Claude, Stéphane (Applied Computational Electromagnetics Society Journal (ACES), 2021)
We present an ultra-wide extended Kband (18 GHz – 30 GHz) planar linear tapered slot antenna (LTSA) design. From a parametric study involving eight designs, the best compromise LTSA is selected in terms of flattest gain and beam width and most symmetric beam width. The design is antipodal with alumina (?r = 10) substrate and fed with substrate integrated waveguide (SIW). Regular corrugations improve cross-polarization, input return loss, and gain. Numerical simulations use finite element analysis and time domain finite integration technique field solvers. The resulting design has half power beam widths (HPBW) of only ± 3.2° and ± 2.5° variation in frequency in the E- and H-planes, respectively. Cross-polarization levels at boresight are 35.7 dB at 18 GHz and 17.4 dB at 30 GHz, return loss is better than -11.7 dB and gain is 9.23 dB with ± 0.40 dB variation with frequency. Alternatively, for imaging systems requiring efficient illumination of a reflector or focusing elements, a second resulting design shows near-perfect beam symmetry with HPBWE/HPBWH = 0.91. These two LTSAs are good candidates for dual-polarization focal plane array feed applications in astronomy imaging.